2016
DOI: 10.1186/s12885-016-2406-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of circulating tumor cell apoptosis and clusters in serial blood samples from patients with metastatic breast cancer in a prospective observational cohort

Abstract: BackgroundPresence of circulating tumor cells (CTCs) is a validated prognostic marker in metastatic breast cancer. Additional prognostic information may be obtained by morphologic characterization of CTCs. We explored whether apoptotic CTCs, CTC clusters and leukocytes attached to CTCs are associated with breast cancer subtype and prognosis at base-line (BL) and in follow-up (FU) blood samples in patients with metastatic breast cancer scheduled for first-line systemic treatment.MethodsPatients with a first met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 40 publications
6
120
2
1
Order By: Relevance
“…One such study enrolled 97 patients with SCLC and found that 32% of patients were positive for CTC clusters, and the presence of CTC clusters at baseline indicated shorter progression-free survival and overall survival (11). An additional prognostic value of CTC clusters in patients with elevated CTCs were reported in two prospective cohorts of advanced stage or metastatic breast cancer (78,79). Furthermore, information regarding CTC clusters were indicative of the failure of chemotherapy treatments in colorectal cancer (60).…”
Section: Clinical Application Of Ctc Clustersmentioning
confidence: 90%
“…One such study enrolled 97 patients with SCLC and found that 32% of patients were positive for CTC clusters, and the presence of CTC clusters at baseline indicated shorter progression-free survival and overall survival (11). An additional prognostic value of CTC clusters in patients with elevated CTCs were reported in two prospective cohorts of advanced stage or metastatic breast cancer (78,79). Furthermore, information regarding CTC clusters were indicative of the failure of chemotherapy treatments in colorectal cancer (60).…”
Section: Clinical Application Of Ctc Clustersmentioning
confidence: 90%
“…Although they typically represent a minority of the CTCs found in the peripheral circulation, they have a metastatic potential that has been estimated to be 23 to 50 times greater than that of their single-cell counterparts [21]. In addition, the presence of CTC clusters and cluster size are associated with worse clinical outcome than the presence of single CTCs in multiple cancer types [17,21,[47][48][49][50]. Although the existence of CTC clusters has been known for decades [51][52][53][54][55], the biological mechanisms behind their formation, survival, dissemination, and superior metastatic ability are only partially understood [48].…”
Section: Single Ctcs Versus Ctc Clustersmentioning
confidence: 99%
“…In patients with ≥5 CTC/7.5 mL blood at baseline, morphologic characterization of persistent CTCs could be an important prognostic marker during treatment, in addition to CTC enumeration alone. 52 It was also recently reported that mitotic CTCs are relativity common in aggressive late-stage breast cancer and may significantly correlate with shortened OS. 53 Many studies so far have confirmed a lack of concordance in HER2 status between tumor tissue and CTCs that may be correlated with the time interval between tissue and CTC HER2 testing.…”
Section: Breast Cancermentioning
confidence: 91%
“…Patients with a continuous presence of apoptotic or clustered CTCs in follow‐up samples after systemic therapy initiation had worse prognosis than patients without these CTC characteristics. In patients with ≥5 CTC/7.5 mL blood at baseline, morphologic characterization of persistent CTCs could be an important prognostic marker during treatment, in addition to CTC enumeration alone . It was also recently reported that mitotic CTCs are relativity common in aggressive late‐stage breast cancer and may significantly correlate with shortened OS …”
Section: Circulating Tumor Cellsmentioning
confidence: 99%